Comparison between High-Sensitivity Cardiac Troponin T and Cardiac Troponin I in a Large General Population Cohort. (4th January 2020) - Welsh, Paul; Preiss, David; Shah, Anoop S V; McAllister, David; Briggs, Andrew; Boachie, Charles; McConnachie, Alex; Hayward, Caroline; Padmanabhan, Sandosh; Welsh, Claire; Woodward, Mark; Campbell, Archie; et al.
Abstract: BACKGROUND: Few data compare cardiac troponin T (cTnT) and cardiac troponin I (cTnI) in a general population. We sought to evaluate the distribution and association between cTnT, cTnI, and cardiovascular risk factors in a large general population cohort. METHODS: High-sensitivity cTnT and cTnI were measured in serum from 19501 individuals in the Generation Scotland Scottish Family Health Study. Associations with cardiovascular risk factors were compared using age- and sex-adjusted regression. Observed age- and sex-stratified 99th centiles were compared with 99th centiles for cTnT (men, 15.5 ng/L; women, 9.0 ng/L) and cTnI (men, 34.2 ng/L; women, 15.6 ng/L) used in clinical practice. RESULTS: cTnT and cTnI concentrations were detectable in 53.3% and 74.8% of participants, respectively, and were modestly correlated in unadjusted analyses ( R 2 = 21.3%) and only weakly correlated after adjusting for age and sex ( R 2 = 9.5%). Cardiovascular risk factors were associated with both troponins, but in age- and sex-adjusted analyses, cTnI was more strongly associated with age, male sex, body mass index, and systolic blood pressure ( P < 0.0001 for all vs cTnT). cTnT was more strongly associated with diabetes ( P < 0.0001 vs cTnI). The observed 99th centiles were broadly consistent with recommended 99th centiles in younger men and women. After the age of 60 years, observed 99th centiles increased substantially for cTnT, and beyond 70 years of age, the 99th centiles approximately doubled for both troponins. CONCLUSIONS: In the general population, cTnT and cTnI concentrations are weakly correlated and are differentially associated with cardiovascular risk factors. The 99th centiles currently in use are broadly appropriate for men and women up to but not beyond the age of 60 years.